PENGARUH KEPRIBADIAN TERHADAP PRILAKU TIDAK PRODUKTIF DALAM KALANGAN PEGAWAI PEMERINTAHAN - Muhamad Ariff Ibrahim (BJRM (Bongaya Journal of Research in Management), 2018)
Counterproductive work behavior is part of job performance components. This study aims to examine the influence of personality on counterproductive work behavior (CWB) among government servants. A total of 204 respondents participated in this study. This study used International Personality Item Pool (IPIP) to measure personality and the scale of counterproductive work behavior was measured by the two dimensions of (counterproductive work behavior-organization) behavior to the organization (CWB-O) and (counterproductive work behavior-individual) behavior to individual (CWB-I). Results showed that there was a significant relationship between CWB and personality. Findings also indicated that agreeableness was a significant predictor to CWBS, CWBI and CWBO among government servants.